Study of 3-prong hadronic tau decays with charged kaons - Richichi, S; Severini, H; Skubic, P; Undrus, A; Bishai, M; Chen, S; Fast, J; Hinson, J; Menon, N; Miller, D; Shibata, E; Shipsey, I; et al. (1999)
Using a sample of 4.7 fb-1 integrated luminosity accumulated with the CLEO-II detector at the Cornell Electron Storage Ring (CESR), we have measured the ratios of the branching fractions B(τ-→K-h+π-ν τ)/B(τ-→h-h+h -ντ)=(5.16±0.20±0.50) × 10-2, B(τ-→K-h+π-π 0ντ)/B(τ- →h-h+h-π0ν τ)=(2.54±0.44±0.39) × 10-2, B(τ-→K-K+π-ν τ)/B(τ-→h-h+h -ντ)=(1.52±0.14 ±0.29) × 10-2, and the upper limit B(τ-→K-K+π-π 0ντ)/B(τ-→h-h +h-π0ντ)<0.0154 at 95% C.L. Coupled with additional experimental information, we use our results to extract information on the structure of three-prong tau decays to charged kaons. ©1999 The American Physical Society.